Low-dose cyclophosphamide depletes circulating naïve and activated regulatory T cells in malignant pleural mesothelioma patients synergistically treated with dendritic cell-based immunotherapy - Noordam, Lisanne (Oncoimmunology, 2018)
Rationale: Regulatory T cells (Treg) play a pivotal role in the immunosuppressive tumor micro-environment in cancer, including mesothelioma. Recently, the combination of autologous tumor lysate-pulsed dendritic cells (DC) and metronomic cyclophosphamide (mCTX) was reported as a feasible and well-tolerated treatment in malignant pleural mesothelioma patients and further as a method to reduce circulating Tregs. Objectives: The aim of this study was to establish the immunological effects of mCTX alone and in combination with DC-based immunotherapy on circulating Treg and other T cell subsets in mesothelioma patients. Methods: Ten patients received mCTX and DC-based immunotherapy after chemotherapy (n = 5) or chemotherapy and debulking surgery (n = 5). Peripheral blood mononuclear cells before, during and after treatment were analyzed for various Treg and other lymphocyte subsets by flow cytometry. Results: After one week treatment with mCTX, both activated FoxP3(hi) and naïve CD45RA(+) Tregs were effectively decreased in all patients. In addition, a shift from naïve and central memory towards effector memory and effector T cells was observed. Survival analysis showed that overall Treg levels before treatment were not correlated with survival, however, nTreg levels before treatment were positively correlated with survival. After completion of mCTX and DC-based immunotherapy treatment, all cell subsets returned to baseline levels, except for the proportions of proliferating EM CD8 T cells, which increased. Conclusions: mCTX treatment effectively reduced the proportions of circulating Tregs, both aTregs and nTregs, thereby favoring EM T cell subsets in mesothelioma patients. Interestingly, baseline levels of nTregs were positively correlated to overall survival upon complete treatment.